The utility of low-iodine diet in preparation for thyroid cancer therapy with radioactive iodine—A cohort study - Luo, Hongxiu; Tobey, Andrew; Auh, Sungyoung; Cochran, Craig; Behairy, Noha; Merino, Maria; Zemskova, Marina; Klubo-Gwiezdzinska, Joanna (Frontiers in Pharmacology, 2022)
Objective: A low iodine diet (LID) of <50ug iodine/day is recommended as preparation for radioactive iodine (RAI) therapy in patients with differentiated thyroid cancer (DTC). The 24-hour urinary iodine excretion (UIE) is utilized to evaluate iodine-deplete status. The aim of this study was to test the association between UIE and progression-free-survival (PFS). Patients and Methods: 70 patients with intermediate-or-high-risk DTC, post total-thyroidectomy, adhered to two weeks of LID and had UIE measured before RAI therapy. Cox regression model was performed to study the contribution of UIE on PFS. Results: The study group consisted of 68% (48/70) women, aged 41.5 [IQR 31.0, 54.0] years, tumor size 2.8 [IQR 1.8-4.5] cm, presence of distant metastases in 22.9% (16/70) of patients. Patients were treated with 1 to 5 RAI dosages with median cumulative activity of 150 [IQR 102-314] mCi (5.5 [IQR 3.8-11.6] GBq). During the follow-up of 3.7 [IQR 1.5-6.5] years, 21.4% (15/70) of patients had disease progression. The risk of progression was significantly higher in patients with UIE ≥ 200 µg/day at the time of RAI administration compared to those with UIE <200 µg/day (HR 3.35, 95% CI 1.09-10.34, P = 0.02). However, multivariate Cox proportional hazards regression analysis adjusted for age, tumor size and presence of distant metastases, suggested that only distant metastases were independently significantly associated with the risk of progression (HR 5.80 (1.17-28.67), P = 0.03). Conclusions: Although the UIE ≥200µg/day might be associated with worse PFS in RAI-treated DTC patients, the presence of distant metastases is a stronger independent predictor of progression. Less stringent LID might be sufficient to achieve the UIE of <200µg/day.